Pengaruh Tingkat Pendidikan, Umur Usaha dan Pengetahuan Akuntansi Terhadap Penggunaan Informasi Akuntansi Pada Usaha Kecil Menengah di Labuhanbatu - Nasution, Irda Ramanda; Prayoga, Yudi; Ihsan, M. Ali Al (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research endeavors to examine and evaluate the methods in which Labuhanbatu’s small and medium-sized enterprises utilize accounting data, accounting for variables including business age, educational attainment, and accounting proficiency. The research population was 432 inhabitants of UKM’s locale, Labuhanbatu. The sample size consisted 81 people, the sampling technique used the Slovin equation. In order to collect data, 81 Google Forms were sent to small and medium-sized organizations. Multiple regression analysis SPSS 20 were used for data analysis. The study’s conclusions show that business age, educational achievement, accounting knowledge all have an impact on how accounting information. Accounting knowledge can impact how accounting information is used. However, the utilization accounting information.